(untitled) (The Pakistan Development Review, 1979)
The paper examines the relationship not only between private investment and financial linkage variables but also amongst the linkage variables. It examines the effect of different policy instruments on investment to provide guidelines to monetary authorities. It shows that the private investment in Pakistan was linked with the availability rather than the price of funds.